(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Salt-sensitivity is more common in blacks than whites but the underlying cause is not fully known. Atrial natriuretic peptide (ANP) concentrations might play a role. This study investigated plasma ANP concentrations and effect of salt-loading in salt-sensitive (SS) and salt-resistant (SR) normotensive (NT) and hypertensive (HT) Nigerians of both genders Forty-three (43) apparently healthy (NT) adult volunteers and thirty-seven (37) age-matched newly diagnosed (HT) Nigerians were grouped into SS and SR volunteers based on the mean changes in their mean arterial blood pressure ≥ 5 mmHg, following a 5-day administration of 200 mmol of sodium in each of the volunteers. ANP concentrations were determined before and after salt loading. Prevalence of SS and SR in the NT and HT Nigerians was 51.2% and 48.8%, respectively. Basal ANP levels in SS and SR NT and HT participants were similar but salt significantly raised ANP concentrations in SS (p < 0.01), SR (p < 0.001) NT volunteers only. Besides, basal ANP concentrations observed in SS and SR NT and HT males and females were similar but salt loading significantly increased ANP levels in SS NT males (p <0.05), SR NT (p < 0.001) and HT (p < 0.05) females only. These findings showed that salt-sensitive hypertensive individuals demonstrated a blunted ANP response to salt loading. However, salt-resistant normotensive volunteers showed a significant increase in ANP concentrations. with higher levels in NT females than males. The impaired ANP response to salt challenge might be the basis for the higher prevalence of salt-sensitivity among blacks.